Penerapan “Blind SAIH” dalam 7 Kebiasaaan Anak Indonesia Hebat untuk Meningkatkan Penguatan Karakter Murid Hambatan Penglihatan - Nickita Kiki Praditya (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Best practice to support the implementation of 7 KAIH is carried out by making modifications to the Great Indonesian Children's Gymnastics (SAIH) for students with visual impairments. Modifications to the Great Indonesian Children's Gymnastics "Blind SAIH" for students with visual impairments are carried out without changing the essence of the original movements. Modifications are made to the movement modifications, the use of clues for each movement transition and modifications to the count. The application of "Blind SAIH" is implemented every day in the Department of Blindness SLB Negeri 1 Bantul. The method in writing this best practice uses a qualitative descriptive approach. The stages in this best practice activity consist of the preparation stage, the implementation stage and the evaluation stage. The author gave a questionnaire to students regarding the evaluation of the implementation of "Blind SAIH" in particular which was then analyzed and used as a basis for determining conclusions. Based on the results of the questionnaire, it was found that there was an increase in awareness of exercise. Students who had a strengthening character in enjoying exercise used from 55 to 80, using five indicators of independence assessment: very poor, less, sufficient, good and very good. Based on these indicators, it was known that the strengthening of the character to like exercise in students can increase. Thus, it can be concluded that the modification of "Blind SAIH" can increase the strengthening of the character of liking exercise in students with special needs.